2021
DOI: 10.1371/journal.pbio.3001158
|View full text |Cite
|
Sign up to set email alerts
|

Disparate temperature-dependent virus–host dynamics for SARS-CoV-2 and SARS-CoV in the human respiratory epithelium

Abstract: Since its emergence in December 2019, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has spread globally and become a major public health burden. Despite its close phylogenetic relationship to SARS-CoV, SARS-CoV-2 exhibits increased human-to-human transmission dynamics, likely due to efficient early replication in the upper respiratory epithelium of infected individuals. Since different temperatures encountered in the human upper and lower respiratory tract (37°C and 33°C, respectively) have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 69 publications
(100 reference statements)
8
111
2
Order By: Relevance
“…The anatomical distance and ambient temperature between upper and lower human respiratory tracts have a profound influence on the replication kinetics of respiratory viruses ( Corman et al, 2016 ; Tyrrell and Bynoe, 1965 ; Holwerda et al, 2019 ; Kendall et al, 1962 ). In agreement with other studies, we observed SARS-CoV-2 growth in favour of lower temperature (35 °C) which can be attributed to the temperature preference of SARS-CoV-2 S protein for its folding and transport ( V'kovski et al, 2020 ; Laporte et al, 2020 ). Both primary HtAEC and HsAEC cultures are shown to be a robust model for SARS-CoV-2 replication that can be used for antiviral drug profiling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The anatomical distance and ambient temperature between upper and lower human respiratory tracts have a profound influence on the replication kinetics of respiratory viruses ( Corman et al, 2016 ; Tyrrell and Bynoe, 1965 ; Holwerda et al, 2019 ; Kendall et al, 1962 ). In agreement with other studies, we observed SARS-CoV-2 growth in favour of lower temperature (35 °C) which can be attributed to the temperature preference of SARS-CoV-2 S protein for its folding and transport ( V'kovski et al, 2020 ; Laporte et al, 2020 ). Both primary HtAEC and HsAEC cultures are shown to be a robust model for SARS-CoV-2 replication that can be used for antiviral drug profiling.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrate that ex vivo models reconstituted from human tracheal or small airway epithelium are permissive for SARS-CoV-2 infection and robustly produces viral progenies from the apical side in long-term experiments (up to 14 days p.i.). Recent studies have also reported on the effect of different SARS-CoV-2 isolates and incubation temperatures on virus replication kinetics ( Corman et al, 2016 ; Pohl et al, 2021 ; V'kovski et al, 2020 ; Zhu et al, 2020 ). We tested two isolates, BavPat1 and GHB-03021, and found that BavPat1 proved to be more infectious.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not evaluate viral load by plaque assay, other studies that measured SARS-CoV-2 titer during replication in similar culture systems also observed a period of exponential replication at the start of infection, consistent with our results. However, not unexpectedly, the reported kinetics vary with experimental conditions, such as viral load in the inoculum and incubation temperature ( Hou et al, 2020 ; Zhu et al, 2020 ; V’kovski et al, 2021 ). Thus, we sought to estimate the replication kinetics in vivo using serial patient samples.…”
Section: Resultsmentioning
confidence: 99%
“…Human bronchial epithelial cells differentiate into functional ciliated and secretory cells in ALI cultures to form a pseudostratified epithelium capable of mucus production and cilia movement (241). They are efficiently infected by SARS-CoV-2 and produce high viral titers enabling functional studies and drug screening [ (14,82,242); Figure 2]. In addition, a LOC model of the human bronchial epithelium under constant flow in the blood vessel chamber has recently been developed to study influenza A virus and SARS-CoV-2 infection and has led to the identification of candidate antiviral compounds (243).…”
Section: Modeling Sars-cov-2 Infection and Pathogenesis In The Respiratory Tractmentioning
confidence: 99%